The Relationship Between Adolescent Social Determinants Factors at the Various Parental Activities on Self-Efficacy for Choosing Healthy Foods - Abadi, Moh Fairuz; Wati, Ni Made Nopita; Prasetya, Didik; Prihatiningsih, Diah; Idayani, Sri; Mirayanti, Ni Ketut Ayu; Pamungkas, Mohammad Adreng (YCAB Publisher, 2024)
Background:Adolescent self-efficacy in choosing healthy foods is closely related to the incidence of obesity. According to WHO data, the obesity rate among children and adolescents increased from 18% to 19.3% between 2016 and 2021, and this rising trend is also observed in Indonesia. Understanding the factors that influence adolescents' eating habits is essential for comprehending their behavior in selecting healthy foods and designing effective interventions to promote healthier eating habits among this age group. Objective:This study aimed to determine the level of adolescent self-efficacy in choosing healthy foods and to examine the relationship between various social determinants such as gender, class, age, and parental activities and adolescent self-efficacy in selecting healthy foods. Additionally, this study tested parental activities as a moderating variable for factors significantly influencing adolescent self-efficacy in choosing healthy foods. Methods:A quantitative descriptive design was employed for this study. The population consisted of high school students, with a total of 408 respondents selected through non-probability cluster sampling. Data were analyzed using univariate, bivariate, and multivariate regression statistical tests. Results:The findings revealed that 57.8% of respondents exhibited a moderate level of self-efficacy in choosing healthy foods, 35.5% showed a strong level of self-efficacy, and 6.6% demonstrated a low level of self-efficacy. Age was the only variable significantly influencing adolescents' ability to choose healthy foods, with a significance level of 0.039 (P < 0.05). Parental activities were not found to significantly moderate the relationship between age and the level of self-efficacy in choosing healthy foods. Conclusion:Age is a significant factor influencing adolescent self-efficacy in choosing healthy foods. However, parental activities do not significantly moderate the relationship between age and adolescent self-efficacy in food selection. Keywords:Adolescent, Feeding Behavior, Meals, Parents, Social Determinants of Health.